2015
DOI: 10.5539/ass.v11n10p73
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality and Customer Satisfaction: A Case Study of Hotel Industry in Vietnam

Abstract: The purpose of this study is to empirically examine the relationship between service quality and customer satisfaction in Vietnamese hotels, survey questionnaire was constructed with 23 service quality items covering 5 service quality dimensions based on SERVQUAL model. Data were collected from 432 guests of 33 three-star hotels in Vietnam in 2013. Analysis results indicate that Reliability, Responsiveness, Assurance, and Empathy significantly impact on the customer satisfaction. The study implies that service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 31 publications
2
12
1
4
Order By: Relevance
“…The probability value was less than 5% at 0.000 < 0.05 and indicated that assurance has a positive effect on community satisfaction. This corresponded with research conducted by Nguyen, M., et al, (2015), Francis, J. & Richard, F. (2017), and Mudenda, C., & Guga, D. (2017) which stated that a company's ability to foster a guaranteed trust in customers through friendliness and knowledge of staff during service provision will impact community satisfaction [10], [11], [12].…”
Section: Multiple Regression Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…The probability value was less than 5% at 0.000 < 0.05 and indicated that assurance has a positive effect on community satisfaction. This corresponded with research conducted by Nguyen, M., et al, (2015), Francis, J. & Richard, F. (2017), and Mudenda, C., & Guga, D. (2017) which stated that a company's ability to foster a guaranteed trust in customers through friendliness and knowledge of staff during service provision will impact community satisfaction [10], [11], [12].…”
Section: Multiple Regression Analysissupporting
confidence: 78%
“…Reliability, Responsiveness, Assurance, Tangibility and Empathy have a significant impact on customer satisfaction. This implies that service quality plays an important role in driving higher levels of customer satisfaction [10], [11], [12].…”
Section: Service Qualitymentioning
confidence: 99%
“…Oleh karena itu pada level 5%, H4 dan H5 ditolak. Pengaruh assurance yang tidak secara signifikan memberi dampak pada customer satisfaction sesuai dengan beberapa penelitian sebelumnya yaitu (Minh et al 2015). Faktor empathy tidak memiliki pengaruh yang positif pada kepuasan konsumen (Suharto dan Sulistiyono, 2015).…”
Section: Metode Penelitianunclassified
“…terhadap kepuasan pelanggan. Menurut penelitian yang telah dilakukan oleh Minh et al (2015) memperlihatkan kualitas layanan memiliki pengaruh yang positif dan signifikan dengan kepuasan pelanggan. Menurut Danish et al (2018) mengatakan bahwa kualitas layanan memiliki pengaruh positif dan signifikan terhadap kepuasan pelanggan.…”
Section: Gambar 1 Kerangka Konseptualunclassified
“…Hasil penelitian ini sesuai dengan Hipotesis satu (H2) yang di ajukan dan diteliti oleh Niaam & Adhimmum (2016) didapatkan hasil bahwa kualitas layanan berpengaruh positif dan signifikan terhadap kepuasan pelanggan. Menurut penelitian yang telah dilakukan oleh Minh et al (2015) memperlihatkan kualitas layanan memiliki pengaruh yang positif dan signifikan dengan kepuasan pelanggan. "…”
Section: Tabel 13 "Hasil Uji Heteroskedastisitas"unclassified